2020
DOI: 10.1007/s00404-020-05847-1
|View full text |Cite|
|
Sign up to set email alerts
|

Preoperative quality of life as prediction for severe postoperative complications in gynecological cancer surgery: results of a prospective study

Abstract: Purpose The aim of this study was to investigate preoperative quality of life (QoL) as a predictive tool for severe postoperative complications (POC) in gynecological cancer surgery. Methods This is a prospective study of patients undergoing gynecologic cancer surgery at an academic center in Germany. QoL was assessed by the EORTC Quality of Life Questionnaire (QLQ-C30) and the NCCN Distress Thermometer (DT). Several geriatric assessment tools have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Several publications focusing on ovarian cancer showed obesity as a highly predictive factor for postoperative complications [10,[26][27][28][29][30][31][32]. Extreme BMIs-both high and low, have been found to be associated with severe postoperative complications [10].…”
Section: Discussionmentioning
confidence: 99%
“…Several publications focusing on ovarian cancer showed obesity as a highly predictive factor for postoperative complications [10,[26][27][28][29][30][31][32]. Extreme BMIs-both high and low, have been found to be associated with severe postoperative complications [10].…”
Section: Discussionmentioning
confidence: 99%
“…The high patient satisfaction should be weighed against the low cost of $50 for each ACP ® double syringe system. It is important to consider that improving quality of life may counteract cancer-related cognitive impairment for cancer survivors [ 17 , 18 ]. The use of PRP should at least be considered and offered to patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous publications, we demonstrated that restrictions in QoL domains such as physical functioning had a significant effect on the risk of severe postoperative complications [ 11 , 12 ]. Furthermore, we found that patients with debilitating symptoms and cognitive impairment had an increased risk of developing severe postoperative complications [ 11 ]. Further work in our institution showed that objective and self-reported cognitive functioning, together with appetite loss, were prognostic for mortality in elderly cancer patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous works demonstrated a strong association between the physical part of the EORTC QLQ-C30 and severe postoperative complications [ 11 , 12 , 13 ]. In particular, functioning domains such as low physical ability and some specific symptoms, most notably, pain, fatigue, and loss of appetite, were associated with poorer survival in cancer patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%